Experiments towards resolving the proton charge radius puzzle - Antognini, A. (2018)
279765, by the FCT, Portugal under Contract No. SFRH/BPD/76842/2011 SFRH/BPD/74775/2010, through the projects No. PEstOE/FIS/UI0303/2011, PTDC/FIS/117606/2010, SFRH/BPD/92329/2013 and SFRH/BD/52332/2013. We acknowledge fruitful discussions with J. Arrington, N. Barnea, S. Bacca, M. Birse, E. Borie, C. Carslon, M. Distler, M. Gorchtein, C. Ji, S. Karshenboim, J. McGovern, K. Pachucki and S. Schlimme